TINGKATKAN KREATIVITAS ANAK DENGAN STIMULI PERKEMBANGAN OTAK - Mardiyani, Ani (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
Every parent is generally pleased if his son intelligent, smart, Kreative, inovative, lively, funny and fun. Intelligence in addition affected by genetics, can also be influenced by teaching and environmental factors, mainly by providing a stimulus to enhance brain development, and creativity of children. Efforts need to be created by educators, parents and other family members if we want the child's brain develop optimally, and make our children more Kreative. Because it is theoretically possible that the child's brain development can still be optimized before the age of seven years.